Efficacy of topical curcuma longa in the healing of extraction sockets: A split-mouth clinical trial - Kalpa Pandya; Devee Abbinayah; Deepshika Selvakumar; Naveen Jayakumar (Wolters Kluwer Medknow Publications, 2023)
Background: The healing process after dental extraction is influenced by various factors, and finding effective strategies for promoting wound healing and reducing postoperative discomfort remains a challenge. This study aimed to evaluate the effectiveness of topical Curcuma longa gel in reducing pain and promoting wound healing after dental extraction, with the secondary objective of assessing the occurrence of dry sockets. The study was a split-mouth randomized controlled trial conducted at the oral and maxillofacial surgery department over 3 months. Materials and Methods: This split-mouth randomized controlled trial consisted of a total of 21 patients undergoing bilateral extractions. One extraction socket was randomly assigned to the test group, where Curcuma. longa gel was applied, while the contralateral socket served as the control group, receiving a placebo. Pain and wound healing were evaluated using standardized scales on the 3rd and 7th days postextraction. Descriptive statistics, paired t-tests, and unpaired t-tests were performed using the SPSS software version 19. The statistical significance was fixed at P ≤ 0.05. Results: The test group showed significantly higher mean healing scores on the 3rd and 7th days compared to the control group. On the 7th day, the test group had significantly lower mean pain scores than the control group. No cases of dry sockets were observed in either group. Conclusion: Topical Curcuma longa gel demonstrated positive effects in promoting wound healing and reducing pain after dental extraction. Clinicians should consider the use of Curcuma longa gel as a post-extraction medicament, particularly in cases involving multiple or traumatic extractions.